A multilayer composite dental appliance and method of making the same
By using a three-layer gradient structure and multi-layer composite material design and chemical bonding technology, the problems of rapid stress decay, long cycle and poor comfort in invisible aligners have been solved, achieving stable corrective force output and improved comfort.
Patent Information
- Application Number
- CN202611386166.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-11-03
AI Technical Summary
Existing invisible orthodontic materials experience rapid stress decay during wear, making it difficult to maintain sufficient corrective force within a 14-day cycle. This results in a long treatment period, a significant conflict between comfort and corrective force, and serious material aging issues.
The multi-layer composite material design with a three-layer gradient structure consists of an outer layer, a middle layer, and an inner layer made of aromatic polyether thermoplastic polyurethane, a medical-grade hydrolysis-resistant polycarbonate, and an aliphatic polyester thermoplastic polyester elastomer, respectively. Chemical bonding is formed through the co-extrusion melting process of the hydroxyl-terminated hyperbranched polyester to ensure continuous stress output throughout the entire wearing cycle.
It achieves stable orthodontic force output throughout the entire wearing period, shortens the treatment period, improves wearing comfort, avoids interlayer separation and material aging problems, and ensures the stability of the material in the warm and humid oral environment.
Smart Images

Figure CN123025554A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of orthodontic appliance manufacturing technology, and in particular to a multilayer composite material orthodontic appliance and its manufacturing method. Background Technology
[0002] Clear aligner technology represents a significant breakthrough in the field of orthodontics in recent years. However, existing clear aligners still have several shortcomings in practical applications: First, stress relaxation is a significant problem. Existing single-layer orthodontic materials experience rapid stress decay during wear, making it difficult to maintain sufficient corrective force during the 14-day replacement cycle.
[0003] Second, the treatment period is long. Because a single layer of material cannot provide effective corrective force continuously, each treatment step usually requires wearing it for 14 days.
[0004] Third, there is a conflict between comfort and corrective force. Rigid materials have high corrective force but poor comfort; soft materials are comfortable but relax quickly.
[0005] Therefore, there is an urgent need for a multilayer composite orthodontic appliance that can provide stable orthodontic force throughout the entire wearing period, shorten the treatment period, improve wearing comfort, and avoid interlayer separation and material aging problems to solve the above problems. Summary of the Invention
[0006] The purpose of this invention is to provide a multilayer composite dental appliance and its preparation method. Through a three-layer gradient structure design of outer, middle and inner layers, combined with the migration and enrichment of terminal hydroxyl hyperbranched polyester to the interlayer interface during co-extrusion melting, the three-layer material is transformed from a physically bonded to a chemically bonded integrated structure. This reduces the stress relaxation rate and ensures that the effective orthodontic force is continuously output throughout the wearing period, thereby shortening the treatment period. The combination of medical-grade hydrolytically resistant polycarbonate in the middle layer and carbodiimide hydrolysis stabilizer ensures that the modulus of the rigid skeleton layer does not decrease in the humid and hot environment of the oral cavity, providing a guarantee for the long-term continuous performance of the gradient structure and interfacial chemical bonding.
[0007] To achieve the above objectives, the present invention provides a multilayer composite material orthodontic appliance, comprising an outer layer, a middle layer and an inner layer sequentially laminated together, wherein the tensile elastic modulus of the middle layer is greater than that of the outer layer and the inner layer. The outer layer, by weight, comprises the following raw materials: 30-50 parts aromatic polyether thermoplastic polyurethane, 0.5-3 parts hydroxyl-terminated hyperbranched polyester, 0.1-0.5 parts hindered phenolic antioxidant, and 0.1-0.5 parts lubricant; The intermediate layer, by weight, comprises the following raw materials: 20-40 parts hydrolysis-resistant polycarbonate, 0.3-2 parts hydroxyl-terminated hyperbranched polyester, 0.1-0.5 parts hindered phenolic antioxidant, and 0.1-0.5% of carbodiimide hydrolysis stabilizer by weight of the total intermediate layer raw materials. The inner layer, by weight, comprises the following raw materials: 25-45 parts aliphatic polyester thermoplastic polyester elastomer, 0.5-3 parts hydroxyl-terminated hyperbranched polyester, 0.1-0.5 parts hindered phenolic antioxidant, and 0.1-0.5 parts lubricant.
[0008] Preferably, the tensile modulus of the outer layer is 1800-2200 MPa, the tensile modulus of the middle layer is 2300-3000 MPa, and the tensile modulus of the outer layer is 50-500 MPa.
[0009] Preferably, the aromatic polyether thermoplastic polyurethane has a number average molecular weight of 80,000-150,000, the hydrolysis-resistant polycarbonate is bisphenol A type polycarbonate with a number average molecular weight of 25,000-45,000, and the aliphatic polyester thermoplastic polyester elastomer has a number average molecular weight of 60,000-120,000.
[0010] Preferably, the hydroxyl-terminated hyperbranched polyester has a hydroxyl value of 200-40 mg KOH / g and a number-average molecular weight of 3000-8000; The lubricant is zinc stearate or erucamide, and the carbodiimide hydrolysis stabilizer is a low-precipitation polymeric carbodiimide.
[0011] Preferably, the outer layer thickness is 0.1-0.25 mm, the middle layer thickness is 0.25-0.5 mm, and the inner layer thickness is 0.1-0.3 mm.
[0012] The above-mentioned method for preparing a multilayer composite material orthodontic appliance includes the following steps: S1. Raw material pretreatment: Aromatic polyether thermoplastic polyurethane, hydrolysis-resistant polycarbonate and aliphatic polyester thermoplastic polyester elastomer are dried. S2. Preparation of outer layer masterbatch: Pretreated aromatic polyether thermoplastic polyurethane, hydroxyl-terminated hyperbranched polyester, hindered phenolic antioxidant and lubricant are added to a high-speed mixer and mixed evenly. The mixture is then melt-blended and extruded into granules by a twin-screw extruder to obtain the outer layer masterbatch. S3. Preparation of intermediate layer masterbatch: Pretreated hydrolysis-resistant polycarbonate, hydroxyl-terminated hyperbranched polyester, hindered phenolic antioxidant and carbodiimide hydrolysis stabilizer are added to a high-speed mixer and mixed evenly. The mixture is then melt-blended and extruded into granules using a twin-screw extruder to obtain the outer layer masterbatch. S4. Preparation of inner layer masterbatch: The pretreated aliphatic polyester thermoplastic polyester elastomer, hydroxyl-terminated hyperbranched polyester, hindered phenolic antioxidant and lubricant are added to a high-speed mixer and mixed evenly. The outer layer masterbatch is obtained by melt blending and extrusion granulation through a twin-screw extruder. S5. The prepared outer layer masterbatch, middle layer masterbatch and inner layer masterbatch are added to the three hoppers of the three-layer co-extrusion film extruder, and co-extruded through the co-extrusion die. After cooling and shaping, a three-layer composite film is obtained. S6. After heating the three-layer composite film, press it into shape, cool and trim the edges to obtain a dental appliance.
[0013] Preferably, in S1, the aromatic polyether thermoplastic polyurethane and the aliphatic polyester thermoplastic polyester elastomer are dried at 80-100℃ for 4-6 hours, and the hydrolysis-resistant polycarbonate is dried at 100-120℃ for 4-6 hours.
[0014] Preferably, in S2-S4, the components are melt-blended at 180-220°C.
[0015] Preferably, in S5, the temperature of the co-extrusion die is 200-240℃.
[0016] Preferably, in step S6, the temperature is heated to 140-170°C, and the pressing pressure is 0.4-0.8 MPa.
[0017] By employing a precise gradient arrangement with the outermost layer having the second-highest modulus, the middle layer having the highest modulus, and the innermost layer having the lowest modulus, an ordered stress transfer path is constructed. This path consists of an outer layer of aromatic polyether thermoplastic polyurethane bearing the initial corrective force, a middle layer of medical-grade hydrolysis-resistant polycarbonate providing durable elastic recovery, and an inner layer of aliphatic polyester thermoplastic polyurethane elastomer providing compliant buffering and uniform stress distribution. This avoids abrupt changes and concentrations of stress at the interlayer interfaces. Meanwhile, the terminal hydroxyl hyperbranched polyester, pre-dispersed within each matrix layer, migrates and accumulates towards the interlayer interface during co-extrusion melting. Its terminal hydroxyl groups form a hydrogen bond network with the active groups such as urethane bonds, carbonate bonds, and ester groups at the ends of each polymer chain, and undergo transesterification and urethane-transesterification reactions. This transforms the three independent film layers, which were originally only physically entangled, into an integrated structure with chemical bonds, effectively inhibiting the relative slippage of the polymer chains at the interface under stress. The intermediate layer uses medical-grade hydrolytically resistant polycarbonate combined with carbodiimide hydrolytic stabilizers to continuously inhibit the hydrolytic breakage of carbonate bonds in the warm and humid oral environment, ensuring that the modulus of the rigid skeleton layer does not decrease during long-term wear. This allows the combined effect of the gradient structure and interfacial chemical bonding to continue to play a role throughout the entire orthodontic cycle.
[0018] Therefore, the present invention, employing the above-mentioned multilayer composite material dental appliance and its preparation method, has the following beneficial effects: (1) The three layers of materials have different functions such as wear-resistant transparent load-bearing, rigid skeleton support and soft fit buffer. The orderly stress transmission path is constructed by the precise gradient arrangement of modulus, so that the high corrective force and high wearing comfort that cannot be achieved by a single layer of material can be achieved at the same time.
[0019] (2) The outer layer of aromatic polyether thermoplastic polyurethane and the middle layer of medical-grade hydrolysis-resistant polycarbonate have good modulus matching, which ensures the efficient transfer of stress from the outer layer to the middle skeleton layer; the middle layer and the inner layer of aliphatic polyester thermoplastic polyurethane elastomer have a large difference in modulus, which ensures that the stress is fully buffered by the flexible inner layer after being supported by the skeleton, and avoids the sudden change and concentration of stress at the interlayer interface.
[0020] (3) The terminal hydroxyl hyperbranched polyester is pre-dispersed in the matrix of each layer and migrates to the interlayer interface during the co-extrusion melting process. Its terminal hydroxyl groups form a hydrogen bond network with the active groups at the ends of each polymer chain and undergo ester exchange and urethane exchange reactions, upgrading the three-layer material from physical bonding to chemical bonding integrated structure. This significantly inhibits the relative slippage of the interface of each polymer chain under stress, greatly reduces the stress relaxation rate, and allows the effective corrective force to be continuously output throughout the entire wearing period.
[0021] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0022] Figure 1 This is a comparison chart of the 14-day stress retention rate of samples from Examples 1-3 and Comparative Examples 1-5 of the present invention, which describes a multilayer composite dental appliance and its preparation method. Figure 2 This is a comparison diagram of the peel strength of the composite film of the sample in Examples 1-3 and Comparative Examples 1-5 of the present invention, which describes a multilayer composite dental appliance and its preparation method. Figure 3 This is a comparison diagram of the peel strength of the finished products of Examples 1-3 and Comparative Examples 1-5 of the present invention, which describe a multilayer composite dental appliance and its preparation method. Figure 4 This is a comparison chart of the peel strength retention rate of samples from Examples 1-3 and Comparative Examples 1-5 after 500 bending cycles for a multilayer composite dental appliance and its preparation method according to the present invention. Figure 5 This is a comparison of the light transmittance of samples from Examples 1-3 and Comparative Examples 1-5 of the present invention, which describe a multilayer composite material dental appliance and its preparation method. Detailed Implementation
[0023] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention should be considered equivalent substitutions and are included within the protection scope of the present invention. Furthermore, it should be understood that after reading the contents of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims and are all within the protection scope of the present invention.
[0024] In this document, the term "embodiment" means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The term "embodiment" appearing in various places throughout the specification does not necessarily refer to the same embodiment, nor does it specifically limit its independence or connection with other embodiments. In principle, in this application, as long as there are no technical contradictions or conflicts, the technical features mentioned in each embodiment can be combined in any way to form corresponding implementable technical solutions.
[0025] Unless otherwise defined, the technical terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the use of related terms herein is merely for the purpose of describing particular embodiments and is not intended to limit this application.
[0026] In this invention, unless otherwise specified, all other test materials and instruments are conventional test materials in the field, which can be purchased through commercial channels, and all raw materials used are medical grade.
[0027] Example 1 This invention provides a multilayer composite material orthodontic appliance, comprising an outer layer, a middle layer and an inner layer sequentially laminated together, wherein the tensile elastic modulus of the middle layer is 2400 MPa, the tensile elastic modulus of the outer layer is 2200 MPa, and the tensile elastic modulus of the inner layer is 300 MPa. The outer layer, by mass parts, includes the following raw materials: 40 parts aromatic polyether thermoplastic polyurethane, 2 parts hydroxyl-terminated hyperbranched polyester, 0.3 parts hindered phenolic antioxidant, and 0.3 parts lubricant. The aromatic polyether thermoplastic polyurethane has a number average molecular weight of 100,000, a Shore hardness of 80D, and cytotoxicity ≤1.
[0028] The intermediate layer, by mass, comprises the following raw materials: 30 parts hydrolytically resistant polycarbonate, 1 part hydroxyl-terminated hyperbranched polyester, 0.3 parts hindered phenolic antioxidant, and 0.3% of carbodiimide hydrolytic stabilizer by mass of the total intermediate layer raw materials. The hydrolytically resistant polycarbonate is bisphenol A type polycarbonate with a number average molecular weight of 30,000 and BPA residue ≤5ppm.
[0029] The inner layer, by weight, comprises the following raw materials: 35 parts aliphatic polyester thermoplastic polyester elastomer, 2 parts hydroxyl-terminated hyperbranched polyester, 0.3 parts hindered phenolic antioxidant, and 0.3 parts lubricant. The number average molecular weight of the aliphatic polyester thermoplastic polyester elastomer is 800,000, and its Shore hardness is 85A.
[0030] The hydroxyl-terminated hyperbranched polyester has a hydroxyl value of 300 mg KOH / g and a number-average molecular weight of 5000. The hindered phenolic antioxidant is hindered phenolic antioxidant 1010, and the lubricant is zinc stearate.
[0031] The above-mentioned method for preparing a multilayer composite material orthodontic appliance includes the following steps: S1. Raw material pretreatment: Aromatic polyether thermoplastic polyurethane, hydrolysis-resistant polycarbonate and aliphatic polyester thermoplastic polyester elastomer are dried. Specifically, aromatic polyether thermoplastic polyurethane and aliphatic polyester thermoplastic polyester elastomer are dried at 90℃ for 5 hours, and hydrolysis-resistant polycarbonate is dried at 110℃ for 5 hours.
[0032] S2. Preparation of outer layer masterbatch: Pretreated aromatic polyether thermoplastic polyurethane, hydroxyl-terminated hyperbranched polyester, hindered phenolic antioxidant and lubricant are added to a high-speed mixer and mixed evenly. The mixture is then melt-blended and extruded into granules at 200°C using a twin-screw extruder to obtain the outer layer masterbatch. S3. Preparation of intermediate layer masterbatch: Pretreated hydrolysis-resistant polycarbonate, hydroxyl-terminated hyperbranched polyester, hindered phenolic antioxidant and carbodiimide hydrolysis stabilizer are added to a high-speed mixer and mixed evenly. The mixture is then melt-blended and extruded granulated at 200°C using a twin-screw extruder to obtain the outer layer masterbatch. S4. Preparation of inner layer masterbatch: The pretreated aliphatic polyester thermoplastic polyester elastomer, hydroxyl-terminated hyperbranched polyester, hindered phenolic antioxidant and lubricant are added to a high-speed mixer and mixed evenly. The mixture is then melt-blended and extruded into granules at 200°C using a twin-screw extruder to obtain the outer layer masterbatch. S5. The prepared outer layer masterbatch, middle layer masterbatch and inner layer masterbatch are added to the three hoppers of the three-layer co-extrusion film extruder, and co-extruded through the co-extrusion die at 220°C. After cooling and shaping, a three-layer composite film is obtained. S6. The three-layer composite film is heated to 155°C and pressed into shape under a pressure of 0.6MPa. After cooling and trimming, a dental appliance is obtained.
[0033] Example 2 The only difference between this embodiment and Embodiment 1 is that the outer layer, by mass, includes the following raw materials: 30 parts aromatic polyether thermoplastic polyurethane, 3 parts hydroxyl-terminated hyperbranched polyester, 0.5 parts hindered phenolic antioxidant, and 0.5 parts lubricant.
[0034] The intermediate layer, by mass, comprises the following raw materials: 40 parts hydrolysis-resistant polycarbonate, 2 parts hydroxyl-terminated hyperbranched polyester, 0.5 parts hindered phenolic antioxidant, and 0.5% of carbodiimide hydrolysis stabilizer by mass of the total intermediate layer raw materials.
[0035] The inner layer, by weight, includes the following raw materials: 45 parts aliphatic polyester thermoplastic polyester elastomer, 3 parts hydroxyl-terminated hyperbranched polyester, 0.5 parts hindered phenolic antioxidant, and 0.5 parts lubricant. The co-extrusion die temperature is 230°C, and the material is pressed after being heated to 160°C. All other conditions are the same.
[0036] Example 3 The only difference between this embodiment and Embodiment 1 is that the outer layer, by mass, includes the following raw materials: 50 parts aromatic polyether thermoplastic polyurethane, 0.5 parts hydroxyl-terminated hyperbranched polyester, 0.1 parts hindered phenolic antioxidant, and 0.1 parts lubricant.
[0037] The intermediate layer, by mass, comprises the following raw materials: 20 parts hydrolysis-resistant polycarbonate, 0.3 parts hydroxyl-terminated hyperbranched polyester, 0.1 parts hindered phenolic antioxidant, and 0.1% of carbodiimide hydrolysis stabilizer by mass of the total intermediate layer raw materials.
[0038] The inner layer, by weight, includes the following raw materials: 25 parts aliphatic polyester thermoplastic polyester elastomer, 0.5 parts hydroxyl-terminated hyperbranched polyester, 0.1 parts hindered phenolic antioxidant, and 0.1 parts lubricant. The lubricant is erucamide. The co-extrusion die temperature is 210°C, and the material is pressed after being heated to 145°C. All other conditions are the same.
[0039] Comparative Example 1 The only difference between this comparative example and Example 1 is that no terminal hydroxyl hyperbranched polyester was added to the raw materials of each layer; all other conditions were the same.
[0040] Comparative Example 2 The only difference between this comparative example and Example 1 is that it includes a single-layer structure prepared from a single TPU; all other conditions are the same.
[0041] Comparative Example 3 The only difference between this comparative example and Example 1 is that the intermediate layer uses ordinary bisphenol A polycarbonate with approximately 200 ppm BPA residue and no hydrolytic stabilizer is added; all other conditions are the same.
[0042] Comparative Example 4 The only difference between this comparative example and Example 1 is that the co-agent film was heat-treated at 140°C for 4 hours after formation; all other conditions were the same.
[0043] Comparative Example 5 The only difference between this comparative example and Example 1 is that the outer layer uses Shore 85A medical-grade aliphatic polyester TPU elastomer (modulus 300MPa), and the inner layer uses Shore 80D medical-grade aromatic polyether TPU. That is, the materials of the outer and inner layers are interchanged, and all other conditions are the same.
[0044] The performance of the orthodontic appliances prepared in Examples 1-3 and Comparative Examples 1-5 was tested: 1. 14-Day Stress Retention Rate: Five parallel samples of the orthodontic appliance were immersed in artificial saliva (prepared according to ISO / TR 10271 standard) at 37℃ for 14 days. A universal testing machine was used to apply a tensile load to the samples at a loading rate of 10 mm / min until a displacement of 0.5 mm was achieved, followed by unloading. The initial stress and the residual stress after 14 days were measured. The stress retention rate was calculated using the following formula: Stress retention rate = (residual stress after 14 days / initial stress) × 100%.
[0045] 2. Interlayer peel strength: The composite film was cut into strips 15mm wide. Interlayer peel tests were conducted on a universal testing machine using the T-shaped peel method at a peel rate of 50mm / min. The average load during the peeling process was recorded, and the peel strength was calculated using the following formula: Peel strength = average peel load / sample width.
[0046] Peel strength was tested on composite films (co-extruded but not hot-pressed) and finished orthodontic appliances (hot-pressed) separately. Five parallel samples were tested in each group, and the average value was taken.
[0047] 3. Peel strength retention rate after 500 bending fatigue cycles: After immersing the finished orthodontic appliance sample in artificial saliva at 37°C, the bending conditions of daily wearing and removal of the orthodontic appliance were simulated: the sample was repeatedly bent along the longitudinal axis to a deformation angle of 30°, and then returned to its initial state, which was counted as one cycle. After 500 cycles, the residual peel strength of the finished orthodontic appliance was tested using the T-shaped peel method described above, and the retention rate was calculated using the following formula: Peel strength retention rate = (peel strength after 500 bends / initial finished product peel strength) × 100%.
[0048] 4. Transmittance and haze: The composite film was cut into 50mm×50mm samples, and the transmittance and haze values of each example and comparative sample were tested using a transmittance / haze meter (according to GB / T 2410) under a D65 light source.
[0049] 5. Cytotoxicity rating: Following ISO 10993-5 standards, the MTT assay was used to test the cytotoxicity of orthodontic appliance materials. Extracts were prepared from each group of samples (extraction medium: DMEM medium containing 10% fetal bovine serum; extraction conditions: 37℃ × 24h), and co-cultured with L929 mouse fibroblasts for 48h. The relative cell growth rate (RGR) was then measured, and the cytotoxicity level was assessed using a 6-point grading system.
[0050] The test results are shown in Table 1 and Figures 1-5 As shown.
[0051] Table 1 Performance Test Results
[0052] - indicates that some indicators are not applicable because the comparative example does not have a double / triple structure (comparative example 2 is a single layer) or does not involve a PC layer (comparative example 2 is a single layer TPU), or comparative example 5 only involves modulus gradient reversal and compatibilizer formulation adjustment and does not involve the intermediate layer material itself.
[0053] From Table 1 and Figures 1-5 It can be seen that the 14-day stress retention rate of Examples 1-3 all reached over 76.8%, significantly better than the comparative examples. This indicates that the present invention, through the synergistic effect of the gradient structure with the highest modulus in the intermediate layer and the pre-embedded layer of hyperbranched polyester with terminal hydroxyl groups, can continuously output stable corrective force during the 14-day wearing cycle, thereby supporting the reduction of the wearing time for each corrective step from the traditional 14 days to 7-10 days. At the same time, the interlayer peel strength (finished product 4.0-4.2 N / cm), the retention rate after 500 bends (85%-88%), the light transmittance (87%-90%), and the haze (≤3%) of each example all showed excellent performance, and the cytotoxicity rating was ≤1, indicating good biocompatibility.
[0054] The only difference between Comparative Example 1 and Example 1 is that no terminal hydroxyl hyperbranched polyester was added to any layer. Its 14-day stress retention rate decreased from 78.6% to 62.3%, and the peel strength of the finished product plummeted from 4.2 N / cm to 0.9 N / cm, a decrease of 79%. Without the terminal hydroxyl hyperbranched polyester, the three matrix materials (aromatic polyether TPU, PC, and aliphatic polyester TPU elastomer) relied solely on physical entanglement. The interfaces rapidly separated after hot pressing and repeated bending, and stress could not be effectively transferred to the PC backbone layer. The role of the terminal hydroxyl hyperbranched polyester is to upgrade the three matrix materials from physical bonding to a chemically bonded integrated structure. Its terminal hydroxyl groups form a network of hydrogen bonds and covalent bonds with the active groups at the ends of the polymer chains in each layer, increasing the peel strength by 4.7 times. This is a direct manifestation of the interfacial chemical synergy between the terminal hydroxyl hyperbranched polyester and the three matrix materials.
[0055] Comparative Example 2, consisting of a single TPU layer, exhibited a 14-day stress retention rate of only 51.7%, significantly lower than the 78.6% of Example 1. The single-layer material lacks the sustained elastic recovery support of the intermediate rigid PC backbone, resulting in rapid stress decay through the segment relaxation of the single polymer network. In the three-layer structure, the outer aromatic polyether-type TPU load-bearing structure, the intermediate rigid PC backbone resisting viscous flow, and the inner aliphatic polyester-type TPU elastomer providing compliant cushioning, all three materials complement each other functionally and are precisely arranged in a gradient of moduli, allowing for orderly stress transmission along the outer-middle-inner layer path. The absence of any one layer would disrupt this stress transmission path, demonstrating the synergy of the three matrix materials in terms of spatial structure and mechanical function.
[0056] After 3 months of immersion in artificial saliva in Comparative Example 3, the molecular weight retention of PC decreased from ≥96% to 88%, a significantly larger decrease; the cumulative release of BPA increased dramatically from ≤0.4 μg / g to 8.6 μg / g, an increase of approximately 20 times; and the light transmittance decreased from 89% to 81%. This indicates that the hydrolysis and breakage of ester bonds in ordinary PC in the warm and humid environment of the oral cavity not only leads to a decrease in molecular weight and a decline in mechanical properties but also releases free BPA, affecting the long-term stability of orthodontic force and posing a biosafety hazard due to long-term contact with the oral mucosa. Using hydrolysis-resistant modified medical-grade PC in combination with a polymeric carbodiimide hydrolysis stabilizer is a necessary means to simultaneously ensure mechanical durability and biosafety.
[0057] The 14-day stress retention rate of Comparative Example 4 increased slightly from 78.6% to 79.1%, an increase of only 0.5 percentage points, which is within the experimental error range. This indicates that the in-situ migration and interfacial reaction of the hydroxyl-terminated hyperbranched polyester during co-extrusion melting were sufficient. The additional post-heat treatment provided almost no benefit to interfacial bonding and stress retention because the migration of the hydroxyl-terminated hyperbranched polyester to the interlayer interface and its chemical bonding with the three-layer matrix material were already fully completed during co-extrusion melting (melt temperature 220℃). Heating at 140℃ in the solid state could not further promote the interfacial reaction. Blindly applying the industry's inherent process of requiring post-heat treatment for multilayer films not only fails to enhance the synergistic effect of raw materials but also seriously damages the core appearance quality of transparent orthodontic appliances. This proves that synergy at the raw material level must be effectively achieved through the correct operating method: "in-situ reaction during co-extrusion melting, rather than induction by post-heat treatment."
[0058] In Comparative Example 5, the 14-day stress retention rate plummeted from 78.6% to 58.4%, a decrease of 20.2 percentage points; the finished product peel strength dropped from 4.2 N / cm to 1.8 N / cm, a decrease of 57%; and the peel strength retention rate after 500 bends decreased from 88% to 58%. This demonstrates that the precise descending modulus order of the middle layer > outer layer > inner layer is a necessary structural design for achieving gradient stress transfer, and not an arbitrary order. When the outer layer modulus is lower than the inner layer modulus, the flexible material of the outer layer cannot effectively transfer the load to the rigid skeleton in the middle. The stress is absorbed by the flexible buffer in the outer layer, failing to utilize the durable elastic recovery function of the PC skeleton layer, leading to a rapid decay of the corrective force. If the order is disordered, the stress transfer path is cut off, and the synergistic effect disappears.
[0059] Therefore, this invention employs a multilayer composite dental appliance and its preparation method. Through a three-layer gradient structure design consisting of an outer layer, a middle layer, and an inner layer, combined with the migration and enrichment of terminal hydroxyl hyperbranched polyester to the interlayer interface during co-extrusion melting, the three-layer material is transformed from a physically bonded to a chemically bonded integrated structure. This reduces the stress relaxation rate and ensures that the effective orthodontic force is continuously output throughout the entire wearing period, thereby shortening the treatment cycle. The combination of medical-grade hydrolytically resistant polycarbonate in the middle layer and carbodiimide hydrolysis stabilizer ensures that the modulus of the rigid skeleton layer does not decrease in the humid and hot environment of the oral cavity, providing a guarantee for the long-term continuous performance of the gradient structure and the chemical bonding at the interface.
[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A multi-layer composite material orthodontic appliance, characterized in that: It consists of an outer layer, a middle layer, and an inner layer that are sequentially composited, with the tensile elastic modulus of the middle layer > the tensile elastic modulus of the outer layer > the tensile elastic modulus of the inner layer. The outer layer, by weight, comprises the following raw materials: 30-50 parts aromatic polyether thermoplastic polyurethane, 0.5-3 parts hydroxyl-terminated hyperbranched polyester, 0.1-0.5 parts hindered phenolic antioxidant, and 0.1-0.5 parts lubricant; The intermediate layer, by weight, comprises the following raw materials: 20-40 parts hydrolysis-resistant polycarbonate, 0.3-2 parts hydroxyl-terminated hyperbranched polyester, 0.1-0.5 parts hindered phenolic antioxidant, and 0.1-0.5% of carbodiimide hydrolysis stabilizer by weight of the total intermediate layer raw materials. The inner layer, by weight, comprises the following raw materials: 25-45 parts aliphatic polyester thermoplastic polyester elastomer, 0.5-3 parts hydroxyl-terminated hyperbranched polyester, 0.1-0.5 parts hindered phenolic antioxidant, and 0.1-0.5 parts lubricant.
2. The orthodontic appliance of multilayer composite material according to claim 1, characterized in that: The tensile modulus of the outer layer is 1800-2200 MPa, the tensile modulus of the middle layer is 2300-3000 MPa, and the tensile modulus of the outer layer is 50-500 MPa.
3. The orthodontic appliance of multilayer composite material according to claim 1, characterized in that: Aromatic polyether thermoplastic polyurethanes have a number average molecular weight of 80,000-150,000, hydrolysis-resistant polycarbonates are bisphenol A type polycarbonates with a number average molecular weight of 25,000-45,000, and aliphatic polyester thermoplastic polyester elastomers have a number average molecular weight of 60,000-120,000.
4. The orthodontic appliance of multilayer composite material according to claim 1, characterized in that: The hydroxyl value of the hydroxyl-terminated hyperbranched polyester is 200-40 mg KOH / g, and the number average molecular weight is 3000-8000. The lubricant is zinc stearate or erucamide, and the carbodiimide hydrolysis stabilizer is a low-precipitation polymeric carbodiimide.
5. The orthodontic appliance of multilayer composite material according to claim 1, characterized in that: The outer layer has a thickness of 0.1-0.25mm, the middle layer has a thickness of 0.25-0.5mm, and the inner layer has a thickness of 0.1-0.3mm.
6. A method for preparing a multilayer composite material orthodontic appliance as described in any one of claims 1-5, characterized in that: Includes the following steps: S1. Raw material pretreatment: Aromatic polyether thermoplastic polyurethane, hydrolysis-resistant polycarbonate and aliphatic polyester thermoplastic polyester elastomer are dried. S2. Preparation of outer layer masterbatch: Pretreated aromatic polyether thermoplastic polyurethane, hydroxyl-terminated hyperbranched polyester, hindered phenolic antioxidant and lubricant are added to a high-speed mixer and mixed evenly. The mixture is then melt-blended and extruded into granules by a twin-screw extruder to obtain the outer layer masterbatch. S3. Preparation of intermediate layer masterbatch: Pretreated hydrolysis-resistant polycarbonate, hydroxyl-terminated hyperbranched polyester, hindered phenolic antioxidant and carbodiimide hydrolysis stabilizer are added to a high-speed mixer and mixed evenly. The mixture is then melt-blended and extruded into granules using a twin-screw extruder to obtain the outer layer masterbatch. S4. Preparation of inner layer masterbatch: The pretreated aliphatic polyester thermoplastic polyester elastomer, hydroxyl-terminated hyperbranched polyester, hindered phenolic antioxidant and lubricant are added to a high-speed mixer and mixed evenly. The outer layer masterbatch is obtained by melt blending and extrusion granulation through a twin-screw extruder. S5. The prepared outer layer masterbatch, middle layer masterbatch and inner layer masterbatch are added to the three hoppers of the three-layer co-extrusion film extruder, and co-extruded through the co-extrusion die. After cooling and shaping, a three-layer composite film is obtained. S6. After heating the three-layer composite film, press it into shape, cool and trim the edges to obtain a dental appliance.
7. The method for preparing a multilayer composite material orthodontic appliance according to claim 6, characterized in that: In S1, aromatic polyether thermoplastic polyurethane and aliphatic polyester thermoplastic polyester elastomer are dried at 80-100℃ for 4-6 hours, and hydrolysis-resistant polycarbonate is dried at 100-120℃ for 4-6 hours.
8. The method for preparing a multilayer composite material orthodontic appliance according to claim 6, characterized in that: In S2-S4, the components are melt-blended at 180-220℃.
9. The method for preparing a multilayer composite material orthodontic appliance according to claim 6, characterized in that: In S5, the temperature of the co-extrusion die is 200-240℃.
10. The method for preparing a multilayer composite material orthodontic appliance according to claim 6, characterized in that: In S6, the temperature is heated to 140-170℃, and the pressing pressure is 0.4-0.8MPa.
